A new species of Daldinia (Xylariaceae) from the Argentine subtropical montane forest - Sir, Esteban Benjamin (2016)
Based on a combination of morphological, molecular phylogenetic and chemotaxonomic evidence, a new species of Daldinia from Northwest of Argentina is described. Daldinia korfii is morphologically related to D. placentiformis, but differs in having brown vinaceous, KOH-extractable pigments and the tissue below the perithecial layer is composed of inconspicuous to conspicuous alternating zones in the new taxon.